THE USE OF INDIGENOUS SYMBOL DESIGN CONCEPT AS A TYPE STYLE FOR FABRICATION OF DISTINCTIVE JEWELLERY TOOL RACK - Addo Tetteh, Nicholas; Mwinnarebu Boroh, Frederick; Kwabena Agyei, Isaac (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The contribution of tools in producing jewellery cannot be over emphasized. In the situation where tools used at the workshop lack the proper place to keep them, they get damaged easily and sometimes not in sight when in need. Production of jewellery items or other forms of work becomes difficult such as tool searching, wrong improvisation of tool usage, time wasting among others when tools are not kept in their proper place. This situation is no different from what the Industrial Art department of the Dr. Hilla Limann Technical University workshop is experiencing. In order to address this problem the study seeks to use Waala and Dagaare indigenous symbols as a source of design concept to produce a customized jewellery tool rack to serve as a jewellery tool keeping device and also enlighten the people on the culture of the Upper West region. This study aimed at identifying and discussing types of tool racks, designing a customized jewellery tool rack using indigenous symbols as the source of idea and producing a customized jewellery tool rack. Descriptive survey and studio-based research approaches were used to outline the processes and methods applied in the study. Purposive and simple random sampling techniques were used to sample jewellery and metal design students (30), technicians (5), lecturers (10), and metal design fabricators (20). A total of 65 participants responded to this study. There were five different indigenous symbols integrated in the final production. Doming, embossing, repousse, piercing, chasing, forging and welding were the fabrication processes employed in this study which were unique in terms of tool rack fabrication. The material used was a combination of aluminum sheet, ungalvanised square pipe and zinc sheet. The study recommends indigenous symbols from different cultures to be used for this type of jewellery tool rack and other much needed items in the workshop so as to give attention to the symbols and in return preserve our culture. Academic institutions should give attention to safe keeping of tools for efficient use by using tool racks purposely for specific tools. Exploration of other materials and techniques for new outcome was also recommended.